NARRATIVAS TRANSMEDIA EN LA COMUNICACIÓN DE LAS ONG. SÍ ME IMPORTA DE OXFAM INTERMÓN - Laura MARTÍNEZ VALERO (Fonseca, Journal of Communication, 2023)
Traditionally, transmedia storytelling has been used for spreading fiction narrative worlds, such as films and TV series. However, it was a matter of time that its ability for explaining the reality was discovered and utilised by social organizations to explain their causes and to reach new audiences. Moreover, the new mobile environment challenges the creativity of the organizations to develop products that make use of this new form of consumption. The Sí me importa campaign, a transmedia project of the Spanish NGO Oxfam Intermón, reclaimed the importance of the international cooperation through social networks, comic, theatre, contemporary art and cinema.